The Features of Mysteria in Religious-Philosophical Tragedies of Milhaud/Claudel - Kaloshina, Galina Ye. (Music Scholarship / Problemy Muzykal’noj Nauki, 2010)
This article examines the influence of philosophical ideas and the concept of theater by Claudel on the compositions for musical-theater by D. Milhaud. They are distinguished by features of so-called polygenre, mounting transfiguration and variable synthesis of multiple art forms, simultaneous and multi-layered dramaturgy, active-variation principle, the Christian tragedy, transfiguration zone in the end of the composition, and the tell-tale signs of mystery. The composition of Milhaud works is related to the development of so called “cover” forms which have meaning of plastic symbols. Keywords: polygenre, conception, Christian tragedy, mystery, mounting transfiguration (variable) synthesis, simultaneous, poly-space dramaturgy processes, «cover» form